Genome-wide analysis of histone modifications in human pancreatic islets - Bhandare, Reena (Cold Spring Harbor Laboratory Press, 2010)
The global diabetes epidemic poses a major challenge. Epigenetic events contribute to the etiology of diabetes; however, the lack of epigenomic analysis has limited the elucidation of the mechanistic basis for this link. To determine the epigenetic architecture of human pancreatic islets we mapped the genome-wide locations of four histone marks: three associated with gene activation—H3K4me1, H3K4me2, and H3K4me3—and one associated with gene repression, H3K27me3. Interestingly, the promoters of the highly transcribed insulin and glucagon genes are occupied only sparsely by H3K4me2 and H3K4me3. Globally, we identified important relationships between promoter structure, histone modification, and gene expression. We demonstrated co-occurrences of histone modifications including bivalent marks in mature islets. Furthermore, we found a set of promoters that is differentially modified between islets and other cell types. We also use our histone marks to determine which of the known diabetes-associated single-nucleotide polymorphisms are likely to be part of regulatory elements. Our global map of histone marks will serve as an important resource for understanding the epigenetic basis of type 2 diabetes.